Inorganic nucleating agent and preparation method thereof and heat-resistant polylactic acid
Surface modification of oyster shell powder with a composite modifier and pretreatments addresses compatibility issues, enhancing the crystallization rate and heat resistance of polylactic acid, thereby improving its mechanical properties and transparency.
Patent Information
- Application Number
- CN202310199681.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-03-04
AI Technical Summary
Inorganic nucleating agents used in polylactic acid suffer from poor compatibility and uneven dispersion, leading to inadequate crystallization nucleation effects, slow crystallization rates, and poor heat resistance, which limits the mechanical properties and application of polylactic acid.
A method involving surface modification of oyster shell powder with a composite modifier comprising a surface modifier and a cross-linking agent, such as aluminate coupling agent, titanate coupling agent, or stearic acid, to enhance compatibility and dispersion in polylactic acid, combined with pretreatments like cellulose fiber and barium sulfate coating to improve crystallization rate and heat resistance.
The modified oyster shell powder effectively enhances the crystallization rate, heat resistance, and transparency of polylactic acid, improving its mechanical strength and application range.
Smart Images

Figure BDA0004108697030000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to an inorganic nucleating agent and a preparation method thereof, and heat-resistant polylactic acid. Background Art
[0002] In recent years, with the improvement of environmental awareness, biodegradable biopolymer materials have received extensive attention, and the development and preparation of such materials have become a hot research topic. Polylactic acid can be prepared by polymerization using lactic acid as the main raw material. The raw material source is sufficient and renewable. Polylactic acid material has high strength, good fluidity, easy molding, and good biodegradability. It is an environmentally friendly material with broad application prospects in the fields of disposable products and packaging materials.
[0003] However, polylactic acid also has shortcomings, such as rigid molecular chains, slow crystallization rate during processing, large shrinkage and brittleness of molded products, which affect the mechanical properties of the products. In addition, polylactic acid has poor heat resistance, which limits its further application.
[0004] To this end, domestic and foreign research has been conducted on how to increase the crystallization rate of polylactic acid, reduce its glass transition temperature, and improve its toughness. Among them, adding a crystallization nucleating agent to increase the crystallization rate of the polymer is a commonly used method in polymer modification processing. Nucleating agents can be divided into two categories: organic and inorganic. Commonly used organic nucleating agents include alkali metal salts containing benzene rings and long-chain fatty carboxylic acid metal salts. These metal salts will cause the degradation of polyester, thereby reducing its mechanical properties and thermal stability. Therefore, inorganic nucleating agents are widely used. Inorganic nucleating agents mainly include montmorillonite, titanium dioxide, calcium oxide, magnesium oxide, etc. The advantage of this type of nucleating agent is that it reaches a micron-level particle size, but there are problems such as poor compatibility with polylactic acid, uneven dispersion and easy agglomeration, and the components cannot play a crystallization nucleation effect. The problems of slow crystallization rate and poor heat resistance cannot be fully solved.
[0005] With respect to the above-mentioned related technologies, the inventors found that the inorganic nucleating agents currently used have poor compatibility with polylactic acid and cannot be dispersed evenly, resulting in the problem that the crystallization nucleation effect cannot be exerted. Summary of the invention
[0006] In order to improve the compatibility of an inorganic nucleating agent with polylactic acid and to increase the crystallization rate and heat resistance of polylactic acid, the present application provides an inorganic nucleating agent and a preparation method thereof and heat-resistant polylactic acid.
[0007] In a first aspect, the present application provides a method for preparing an inorganic nucleating agent, using the following technical solution:
[0008] A method for preparing an inorganic nucleating agent comprises the following steps:
[0009] Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 1-5:1, then add them to an acetone or anhydrous ethanol solution, mix them evenly, and prepare a composite modifier, wherein the volume of the solution is 2-4 times the total volume of the surface modifier and the cross-linking agent; modification of oyster shell powder: take oyster shell powder, add the composite modifier thereto while stirring, mix evenly, filter, and vacuum dry to prepare an inorganic nucleating agent, wherein the addition amount of the composite modifier is 0.3-3% of the oyster shell powder.
[0010] By adopting the above technical scheme, the oyster shell powder is surface treated with a blend of a surface modifier and a cross-linking agent, so that the compatibility of the oyster shell powder with polylactic acid is improved, the powder can be evenly dispersed in the polylactic acid, play a good role in crystallization nucleation, promote the formation of polylactic acid nuclei and the growth of crystallites, refine the crystal size, increase the crystallization rate, and improve the heat resistance and molding processability, oxidation resistance and hydrolysis resistance of polylactic acid products.
[0011] Optionally, the cross-linking agent is selected from one of bismaleimide and polycarbodiimide;
[0012] The surface modifier is selected from one of an aluminate coupling agent, a titanate coupling agent and stearic acid.
[0013] By adopting the above technical scheme, aluminate coupling agent, titanate coupling agent and stearic acid can generate chemical bonds on the surface of oyster shell powder, and act as a bridge between oyster shell powder and polylactic acid. One end of the aluminate coupling agent, titanate coupling agent and stearic acid can react with free protons on the surface of oyster shell powder to generate chemical bonds, and the other end can cause cross-linking reaction of polylactic acid or entanglement by van der Waals force, so that oyster shell powder and polylactic acid become an organic whole; polycarbodiimide and bismaleimide can generate end-capping reaction with hydroxyl or carboxyl end groups in polylactic acid to generate a relatively stable ureide structure, thereby improving the thermal stability of polylactic acid, and improving the hydrolysis resistance and thermal processing stability of polylactic acid.
[0014] Optionally, the method for preparing the oyster shell powder comprises the following steps: washing and grinding the oyster shells to make block oyster shells, and calcining the block at 600-700° C. for 12-24 hours to obtain the oyster shell powder.
[0015] By adopting the above technical scheme, after the oyster shell is calcined, due to the discharge of carbon dioxide and the decomposition of substances, the pores and channels change to form a complex porous structure, so that during the modification, more composite modifiers can be adsorbed, thereby improving the surface modification effect of the oyster shell powder and the crystal nucleation effect of the oyster shell powder.
[0016] Optionally, the block oyster shell is subjected to the following pretreatment before calcination:
[0017] A mixed aqueous solution of sodium sulfate and barium chloride is added to the block oyster shell, stirred for 50-60 minutes, and filtered. The molar ratio of sodium sulfate to barium chloride is 1:0.9-1.1, and the mass ratio of the block oyster shell to sodium sulfate is 1:0.1-0.15.
[0018] After adding nucleating agent to polylactic acid due to its slow crystallization rate, although it can improve heat resistance and durability and increase crystallization rate, the large crystal size will cause the transparency of polylactic acid to decrease, hindering the wide application of polylactic acid in packaging and other fields. By adopting the above technical scheme, the block oyster shell is treated with a mixed aqueous solution of sodium sulfate and barium chloride, and barium sulfate is coated on the surface of the block oyster shell. The main purpose is to form a deposition layer with a sponge structure, produce a certain porosity, improve dispersibility, increase light transmittance, and then increase transparency, thereby preventing the addition of oyster shell powder to polylactic acid from causing the transparency of polylactic acid to decrease.
[0019] Optionally, the vacuum drying temperature is 80-100° C., and the drying time is 12-24 hours.
[0020] Optionally, the oyster shell powder is subjected to the following pretreatment before modification:
[0021] The cellulose fibers, polyacrylamide and deionized water are mixed to prepare a suspension;
[0022] Adding oyster shell powder to the suspension, mixing evenly, filtering, and drying to prepare pretreated oyster shell powder;
[0023] A 15-20wt% polydiallyldimethylammonium chloride solution is evenly sprayed on the surface of the pretreated oyster shell powder, and after drying, the powder is immersed in a 1.5-2wt% microfibrillated cellulose solution at room temperature for 1-2 hours, taken out, and dried at 100-110°C for 1.5-2 hours.
[0024] By adopting the above technical scheme, polyacrylamide is used as a dispersant to evenly disperse the cellulose fibers to form a suspension. After the oyster shell powder is blended in the suspension, the cellulose fibers form a cellulose film on the surface of the oyster shell powder after filtration, and the cellulose film has good transparency, but the cellulose film has a loose stacking structure, and there are many pores between the fibers, which easily lead to an increase in light scattering rate and a decrease in transparency. Therefore, its surface is cationized with polydiallyldimethylammonium chloride and deposited on the cellulose film to make the structure of the cellulose film more compact, reduce the light scattering coefficient, and improve transparency. Then, the negatively charged microfibrillated cellulose is combined with the cationized oyster shell powder with a positive charge by an impregnation method, so as to fill it into the fiber membrane network structure, reduce the air inside the cellulose membrane, thereby reducing the interface between the fiber membrane and the air, eliminating the internal light scattering and reflection, and improving the light transmittance of the oyster shell powder. Moreover, after the impregnation treatment, the structure of the cellulose fiber membrane is compact, the bonding force between the fibers is enhanced, and the mechanical properties of the oyster shell surface are improved.
[0025] Optionally, when the oyster shell powder is pretreated, the weight proportions of the raw materials are as follows: 1-1.5 parts of cellulose fiber, 0.1-0.2 parts of polyacrylamide, 10-15 parts of deionized water, 3-5 parts of oyster shell powder, 0.5-1 parts of
[0026] Polydiallyldimethylammonium chloride solution, 5-8.5 parts of microfibrillated cellulose.
[0027] By adopting the above technical scheme, when the oyster shell powder is pretreated with the above raw materials in various weight portions, the pretreated oyster shell powder is then used with a composite modifier to improve the compatibility, so that a better transparent cellulose film can be formed on the surface of the oyster shell powder, thereby improving the transparency of the oyster shell powder.
[0028] In a second aspect, the present application provides an inorganic nucleating agent, which adopts the following technical solution:
[0029] An inorganic nucleating agent is prepared by a preparation method of the inorganic nucleating agent.
[0030] By adopting the above technical scheme, the inorganic nucleating agent prepared thereby has good compatibility with polylactic acid, can effectively improve the crystallization rate of polylactic acid, and obtain polylactic acid products with excellent heat resistance and good transparency.
[0031] In a third aspect, the present application provides a heat-resistant polylactic acid, which adopts the following technical solution:
[0032] A heat-resistant polylactic acid includes an inorganic nucleating agent prepared by a preparation method of the inorganic nucleating agent.
[0033] By adopting the above technical solution, an inorganic nucleating agent is used to improve the crystallization rate of polylactic acid, thereby improving the crystallization rate, crystallinity, heat deformation temperature, microcaloric softening point and transparency of polylactic acid, thereby making the application range of polylactic acid wider.
[0034] Optionally, the preparation method of the heat-resistant polylactic acid is:
[0035] The polylactic acid is dried at 80-85° C. for 10-12 hours, and then mixed evenly with an inorganic nucleating agent in a mass ratio of 99.7:0.3-97:3, and granulated to obtain heat-resistant polylactic acid.
[0036] By adopting the above technical scheme, the inorganic nucleating agent and the dried polylactic acid are blended in a certain proportion. Within the limit of not destroying the purpose of the present application, commonly used additives such as light stabilizers, lubricants, colorants containing dyes and colors, etc. can also be added. The preparation method is simple and easy to control. The basic raw material source is rich, and the crystallization rate can be significantly improved, and the crystallinity and heat resistance of the polylactic acid products are increased. The polylactic acid products refer to films, sheets, fibers, cloths, non-woven fabrics, injection molded products, extrusion molded products, vacuum pressure molded products, blow molded products, and composites of other materials, etc., which can be used for textiles, packaging, agricultural materials, gardening materials, civil engineering materials, stationery, toys, medical supplies or other purposes.
[0037] In summary, this application has the following beneficial effects:
[0038] 1. Since the present application adopts a mixture of a surface modifier and a cross-linking agent as a composite modifier, the surface of the oyster shell powder is modified, the compatibility of the oyster shell powder and polylactic acid is improved, the oyster shell powder is evenly dispersed in the polylactic acid, the crystallization rate, crystallinity and heat resistance temperature of the polylactic acid are increased, the mechanical strength of the polylactic acid is improved, and the application range of the polylactic acid is wider.
[0039] 2. In the present application, it is preferred to coat the surface of the oyster shell with barium sulfate before calcining, thereby forming a deposition layer with a sponge structure, reducing the porosity of the oyster shell, improving the dispersibility of the oyster shell in the polylactic acid, and increasing the light transmittance of the polylactic acid product, thereby improving the transparency of the polylactic acid product, so as to prevent the addition of oyster shell powder to the polylactic acid product to improve the crystallization rate, thereby causing the transparency of the polylactic acid product to decrease.
[0040] 3. In the present application, it is preferred that before the oyster shell powder is modified, it is first surface treated with cellulose fiber, polydiallyldimethylammonium chloride and microfibrillated cellulose, so that a cellulose film is formed on the surface of the oyster shell powder, and then the cellulose film is cationized with polydiallyldimethylammonium chloride, and the density of the cellulose film is improved, the light scattering coefficient is reduced, and the transparency is improved. Finally, the microfibrillated cellulose is mixed with the cationic cellulose film. The microfibrillated cellulose can reduce the porosity of the cellulose film, reduce internal light scattering and reflection, and improve the light transmittance, so that the polylactic acid added with the oyster shell powder does not decrease in transparency due to the addition of the nucleating agent. DETAILED DESCRIPTION
[0041] Example
[0042] Example 1: An inorganic nucleating agent is prepared by the following method:
[0043] S1. Preparation of oyster shell powder: Wash and grind oyster shells to make block oyster shells, and calcine at 700° C. for 12 h to obtain oyster shell powder, wherein the average particle size of the oyster shell powder is 10 μm;
[0044] S2. Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 1:1, then add them to an acetone solution, mix them evenly, and prepare a composite modifier. The volume of the acetone solution is 4 times the total volume of the surface modifier and the cross-linking agent. The surface modifier is a 101-type titanate coupling agent, and the cross-linking agent is bismaleimide.
[0045] S3. Modification of oyster shell powder: Take oyster shell powder, add a composite modifier thereto while stirring, mix for 5 minutes, filter, and vacuum dry at 100° C. for 12 hours to prepare an inorganic nucleating agent. The addition amount of the composite modifier is 3% of the oyster shell powder.
[0046] Example 2: An inorganic nucleating agent is prepared by the following method:
[0047] S1. Preparation of oyster shell powder: Wash and grind oyster shells to make block oyster shells, and calcine at 600° C. for 14 h to obtain oyster shell powder, wherein the average particle size of the oyster shell powder is 15 μm;
[0048] S2. Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 5:1, add them into an acetone solution, mix them evenly, and prepare a composite modifier. The volume of the acetone solution is twice the total volume of the surface modifier and the cross-linking agent. The surface modifier is an aluminate coupling agent, and the cross-linking agent is polycarbodiimide.
[0049] S3. Modification of oyster shell powder: Take oyster shell powder, add a composite modifier thereto while stirring, mix for 3 minutes, filter, and vacuum dry at 80° C. for 24 hours to prepare an inorganic nucleating agent. The addition amount of the composite modifier is 0.3% of the oyster shell powder.
[0050] Embodiment 3: An inorganic nucleating agent is prepared by the following method:
[0051] S1. Preparation of oyster shell powder: Wash and grind oyster shells to make block oyster shells, and calcine at 650° C. for 18 h to obtain oyster shell powder, wherein the average particle size of the oyster shell powder is 20 μm;
[0052] S2. Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 3:1, add them to an acetone solution, mix them evenly, and prepare a composite modifier. The volume of the acetone solution is 3 times the total volume of the surface modifier and the cross-linking agent. The surface modifier is stearic acid, and the cross-linking agent is polycarbodiimide.
[0053] S3. Modification of oyster shell powder: Take oyster shell powder, add a composite modifier thereto while stirring, mix for 4 minutes, filter, and vacuum dry at 90° C. for 18 hours to prepare an inorganic nucleating agent. The addition amount of the composite modifier is 1.7% of the oyster shell powder.
[0054] Example 4: An inorganic nucleating agent, which is different from Example 1 in that the surface modifier is a silane coupling agent KH550.
[0055] Example 5: An inorganic nucleating agent, which is different from Example 1 in that the cross-linking agent is diisopropylbenzene peroxide.
[0056] Example 6: An inorganic nucleating agent, which is different from Example 1 in that the oyster shell powder is made by washing and grinding oyster shells.
[0057] Example 7: An inorganic nucleating agent, which differs from Example 1 in that, in step S1, the block oyster shell is subjected to the following pretreatment before calcination: a mixed aqueous solution of sodium sulfate and barium chloride is added to the block oyster shell, stirred for 60 minutes until the surface of the block oyster shell is coated with barium sulfate, and filtered. The molar ratio of sodium sulfate to barium chloride is 1:1, the mass ratio of block oyster shell to sodium sulfate is 1:0.15, and the amount of water in the mixed aqueous solution is twice the total weight of sodium sulfate and barium chloride.
[0058] Embodiment 8: An inorganic nucleating agent, which is different from Embodiment 1 in that, in step S3, the oyster shell powder is subjected to the following pretreatment before being modified:
[0059] (1) 1.5 kg of cellulose fiber, 0.2 kg of polyacrylamide and 15 kg of deionized water were mixed to prepare a suspension;
[0060] (2) adding 5 kg of oyster shell powder to the suspension, mixing evenly, filtering, and drying at 80° C. for 6 h to prepare pretreated oyster shell powder;
[0061] (3) 1 kg of a 20 wt% aqueous solution of polydiallyldimethylammonium chloride was uniformly sprayed on the surface of the pretreated oyster shell powder, dried at 50°C for 4 h, immersed in a 2 wt% microfibrillated cellulose solution prepared by 8.5 kg of microfibrillated cellulose at room temperature for 2 h, taken out, and dried at 110°C for 1.5 h.
[0062] Embodiment 9: An inorganic nucleating agent, which is different from Embodiment 1 in that, in step S3, the oyster shell powder is subjected to the following pretreatment before being modified:
[0063] (1) 1 kg of cellulose fiber, 0.1 kg of polyacrylamide and 10 kg of deionized water were mixed to prepare a suspension;
[0064] (2) adding 3 kg of oyster shell powder to the suspension, mixing evenly, filtering, and drying at 80° C. for 6 h to prepare pretreated oyster shell powder;
[0065] (3) 0.5 kg of an aqueous solution of 15 wt% polydiallyldimethylammonium chloride was uniformly sprayed on the surface of the pretreated oyster shell powder, dried at 50°C for 4 h, immersed in a microfibrillated cellulose solution of 1.5 wt% prepared by 5 kg of microfibrillated cellulose at room temperature for 1 h, taken out, and dried at 100°C for 2 h.
[0066] Embodiment 10: An inorganic nucleating agent, which differs from Embodiment 8 in that the pretreatment method of oyster shell powder is as follows:
[0067] (1) 1 kg of cellulose fiber, 0.1 kg of polyacrylamide and 10 kg of deionized water were mixed to prepare a suspension;
[0068] (2) Add 3 kg of oyster shell powder to the suspension, mix well, filter, and dry at 80°C for 6 h.
[0069] Embodiment 11: An inorganic nucleating agent, which is different from Embodiment 8 in that the pretreatment method of oyster shell powder is as follows:
[0070] (1) 1 kg of cellulose fiber, 0.1 kg of polyacrylamide and 10 kg of deionized water were mixed to prepare a suspension;
[0071] (2) adding 3 kg of oyster shell powder to the suspension, mixing evenly, filtering, and drying at 80° C. for 6 h to prepare pretreated oyster shell powder;
[0072] (3) The pretreated oyster shell powder was immersed in a microfibrillated cellulose solution with a concentration of 1.5 wt % prepared by 5 kg of microfibrillated cellulose at room temperature for 1 hour, then taken out and dried at 100° C. for 2 hours.
[0073] Example 12: An inorganic nucleating agent, which differs from Example 8 in that the pretreatment method of oyster shell powder is as follows:
[0074] (1) 1 kg of cellulose fiber, 0.1 kg of polyacrylamide and 10 kg of deionized water were mixed to prepare a suspension;
[0075] (2) adding 3 kg of oyster shell powder to the suspension, mixing evenly, filtering, and drying at 80° C. for 6 h to prepare pretreated oyster shell powder;
[0076] (3) 0.5 kg of a 15 wt % aqueous solution of polydiallyldimethylammonium chloride was uniformly sprayed on the surface of the pretreated oyster shell powder and dried at 50° C. for 4 h.
[0077] Embodiment 13: An inorganic nucleating agent is prepared by the following method:
[0078] S1. Preparation of oyster shell powder: Wash and grind the oyster shell to make a block of oyster shell, add a mixed aqueous solution of sodium sulfate and barium chloride to the block of oyster shell, stir for 60 minutes until the surface of the block of oyster shell is coated with barium sulfate, filter, the molar ratio of sodium sulfate to barium chloride is 1:1, calcine at 700° C. for 12 hours to obtain oyster shell powder, the average particle size of the oyster shell powder is 10 μm;
[0079] S2. Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 1:1, then add them to an acetone solution, mix them evenly, and prepare a composite modifier. The volume of the acetone solution is 4 times the total volume of the surface modifier and the cross-linking agent. The surface modifier is a 101-type titanate coupling agent, and the cross-linking agent is bismaleimide.
[0080] S3, oyster shell powder pretreatment: (1) 1.5 kg of cellulose fiber, 0.2 kg of polyacrylamide and 15 kg of deionized water were mixed to prepare a suspension; (2) 5 kg of oyster shell powder was added to the suspension, mixed evenly, filtered, and dried at 80°C for 6 h to prepare pretreated oyster shell powder; (3) 1 kg of a 20 wt% aqueous solution of polydiallyldimethylammonium chloride was evenly sprayed on the surface of the pretreated oyster shell powder, dried at 50°C for 4 h, immersed in a 2 wt% microfibrillated cellulose solution prepared by 8.5 kg of microfibrillated cellulose at room temperature for 2 h, taken out, and dried at 110°C for 1.5 h;
[0081] S4. Modification of oyster shell powder: Take oyster shell powder, add a composite modifier thereto while stirring, mix for 5 minutes, filter, and vacuum dry at 100° C. for 12 hours to prepare an inorganic nucleating agent. The addition amount of the composite modifier is 3% of the oyster shell powder.
[0082] Comparative Example
[0083] Comparative Example 1: An inorganic nucleating agent, which is different from Example 1 in that no surface modifier is added to the composite modifier.
[0084] Comparative Example 2: An inorganic nucleating agent, which is different from Example 1 in that no crosslinking agent is added to the composite modifier.
[0085] Comparative Example 3: A method for preparing a polylactic acid nucleating agent, comprising the following steps:
[0086] At room temperature, sepiolite with a particle size of 10 μm is put into a 15% hydrochloric acid acid liquid under stirring, the weight ratio of sepiolite to acid liquid is 1:10, after stirring and mixing for 30 minutes, filtered, washed repeatedly 6 times with sodium hydroxide aqueous solution, the concentration of sodium hydroxide aqueous solution is 10%, and dried to obtain high-purity and high-activity sepiolite. The sepiolite is put into a high-speed mixer, diphenylmethane diisocyanate (MDI) is added, the weight ratio of sepiolite to diphenylmethane diisocyanate (MDI) is 10:0.5, solid phase reaction is carried out under the condition of temperature of 150°C, the mixing speed is 200 rpm, the time is 20 minutes, and then the system is cooled to a temperature of 65°C, and then N-cyclohexylmaleimide with a weight ratio of 5.0% is added, and high-speed mixing is carried out for 10 minutes, the mixing speed is 900 rpm, and the machine is stopped for cooling to obtain a nucleating agent.
[0087] Application Examples
[0088] Application Example 1: A heat-resistant polylactic acid is prepared by the following method: polylactic acid is dried at 80°C for 12 hours, then mixed evenly with the inorganic nucleating agent prepared in Example 1 at a mass ratio of 97:3, melted, extruded and granulated at 180°C to obtain heat-resistant polylactic acid. The model of the polylactic acid is 4032D, Mw=207000 g / mol, and the density is 1.25 g / cm 3 , the content of D-lactic acid units is 2%.
[0089] Application Example 2-13: A heat-resistant polylactic acid, which is different from Application Example 1 in that the inorganic nucleating agent is made from Examples 2-13 respectively.
[0090] Application Example 14: A heat-resistant polylactic acid, which is different from Application Example 1 in that the mass ratio of the inorganic nucleating agent to the polylactic acid is 2:98.
[0091] Application Example 15: A heat-resistant polylactic acid, which is different from Application Example 1 in that the mass ratio of the inorganic nucleating agent to the polylactic acid is 0.3:99.7.
[0092] Application Examples 16-17: A heat-resistant polylactic acid, which is different from Application Example 1 in that the inorganic nucleating agent is made from Comparative Example 1 and Comparative Example 2, respectively.
[0093] Application Example 18: A polylactic acid, which is different from Application Example 1 in that the nucleating agent is made from Comparative Example 3, and the mass ratio of the nucleating agent to the polylactic acid is 1:20.
[0094] Performance testing
[0095] Heat-resistant polylactic acid was prepared according to the method in the application example, and then the properties of the heat-resistant polylactic acid were tested according to the following method. The test results are recorded in Table 1.
[0096] 1. Tensile strength: The test was carried out in accordance with GB / T1040.1-2018 "Determination of tensile properties of plastics Part 1 General principles". Five specimens were tested in each group and the results were averaged.
[0097] 2. Fracture strain: According to GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", 5 specimens are tested in each group and the results are averaged.
[0098] 3. Crystallization rate: According to the DSC test method, the thermal analysis was performed using a Q100 differential scanning calorimeter from TA Company of the United States. The sample mass was 3-8 mg. Under nitrogen protection, the temperature was raised from room temperature to 200°C at a rate of 20°C / min, and the temperature was kept for 5 minutes to eliminate the thermal history. Then, the temperature was rapidly lowered to 110°C at a rate of 50°C / min. Isothermal crystallization was performed at 110°C, and the half-crystallization time t was tested. 1 / 2 .
[0099] 4. Heat deformation temperature: Test according to ASTM D648 "Heat deformation temperature of plastics", test 5 specimens in each group and take the average value of the results.
[0100] 5. Transparency: The heat-resistant polylactic acid was hot-melt, extruded, and cast into a film with a thickness of 85 μm, which was cut into samples with a size of 6 cm × 6 cm. The samples were tested using the LAMBDA950 UV / visible / near-infrared photometer of the American PE Company. The wavelength range was selected to be 400-800 nm. The transmittance was used to characterize the transparency of the heat-resistant polylactic acid film. The greater the transmittance, the higher the transparency. Five samples were tested in each group and the results were averaged.
[0101] Table 1
[0102]
[0103] The data in Table 1 show that the inorganic nucleating agents prepared in Examples 1-3 are respectively used in Application Examples 1-3, and the heat-resistant polylactic acid prepared therefrom has good mechanical properties, and the crystallization rate is faster than that of pure polylactic acid, and the heat deformation temperature is high, indicating that the inorganic nucleating agent has good compatibility with polylactic acid, can be evenly dispersed in polylactic acid, and enhances the crystallization rate, mechanical strength and heat resistance of polylactic acid, but the transparency is attenuated.
[0104] In Application Examples 4 and 5, the inorganic nucleating agents prepared in Examples 4 and 5 are used respectively. In Example 4, silane coupling agent KH550 is used instead of titanate coupling agent, and diisopropylbenzene peroxide is used instead of bismaleimide in Example 5. Table 1 shows that the heat-resistant polylactic acid prepared in Application Examples 4 and 5 has worse tensile properties, fracture strain and heat resistance temperature than pure polylactic acid, indicating that the use of titanate coupling agent, aluminate coupling agent or stearic acid as a surface modifier and the use of bismaleimide or polycarbodiimide as a cross-linking agent can effectively improve the compatibility between oyster shell powder and polylactic acid, increase the crystallization rate, and improve the heat resistance of polylactic acid.
[0105] In Application Example 6, the inorganic nucleating agent prepared in Example 6 is used, wherein the oyster shell powder is not calcined. Table 1 shows that the tensile strength and breaking strain of the heat-resistant polylactic acid prepared in Application Example 6 are lower than those in Application Example 1, and the heat-resistant temperature is reduced.
[0106] Compared with Example 1, Application Example 7 uses the inorganic nucleating agent prepared in Example 7. In Example 7, the block oyster shell is treated with a mixed aqueous solution of sodium sulfate and barium chloride before calcination, and the barium sulfate is coated on the block oyster shell. Table 1 shows that compared with Application Example 1, the heat-resistant polylactic acid prepared in Application Example 7 has better heat resistance, crystallization rate and mechanical strength, and the transparency is effectively improved.
[0107] In Application Examples 8 and 9, the inorganic nucleating agents prepared in Examples 8 and 9 were used respectively. Before the oyster shell powder was modified, it was pretreated with cellulose fiber, microfibrillated cellulose and other ingredients. The data in Table 1 showed that the heat-resistant polylactic acid prepared in Application Examples 8 and 9 was similar to that in Application Example 1, with a faster crystallization rate, high mechanical strength, good heat resistance, and improved transparency.
[0108] In Application Example 10, the inorganic nucleating agent prepared in Example 10 is used. Compared with Example 8, in Example 10, polydiallyldimethylammonium chloride and microfibrillated cellulose are not used in the pretreatment of oyster shell powder. Table 1 shows that the other properties of the heat-resistant polylactic acid prepared in Example 10 are not much changed compared with those in Application Example 8, but the light transmittance is obviously reduced.
[0109] In Application Example 11, the inorganic nucleating agent prepared in Example 11 is used. Compared with Example 8, in Example 11, the oyster shell powder pretreated with cellulose fibers is not treated with an aqueous solution of polydiallyldimethylammonium chloride. In Application Example 12, compared with Application Example 8, the pretreated oyster shell powder is not treated with a microfibrillated cellulose solution. The transparency of the heat-resistant polylactic acid prepared in Application Examples 11 and 12 is higher than that in Application Example 10, but still lower than that in Application Example 10. This indicates that pretreatment of the oyster shell powder with cellulose fibers, polydiallyldimethylammonium chloride and microfibrillated cellulose and then modification can effectively improve the transparency of the oyster shell powder, thereby increasing the light transmittance of the polylactic acid and improving the surface gloss.
[0110] In Application Example 13, not only is the blocky oyster shell coated with barium sulfate, but after calcination, the oyster shell powder is also pretreated with cellulose fiber, etc. Compared with Application Example 1, Application Example 7 and Application Example 8, the heat-resistant polylactic acid prepared in Application Example 13 not only has good heat resistance and mechanical strength, but also has high light transmittance and better transparency.
[0111] Compared with Application Example 1, the mass ratio of inorganic nucleating agent to polylactic acid in Application Example 14 is 2:98, and the mass ratio of inorganic nucleating agent to polylactic acid in Application Example 15 is 0.3:99.7. The heat-resistant temperature of the heat-resistant polylactic acid prepared in Application Examples 14 and 15 is reduced, and the mechanical strength is not as good as that in Application Example 1, which indicates that the heat-resistant polylactic acid with better heat resistance and mechanical strength can be obtained by adopting the ratio of inorganic nucleating agent to polylactic acid in Application Example 1.
[0112] In Application Example 16 and Application Example 17, the inorganic nucleating agents prepared in Comparative Example 1 and Comparative Example 2 were used respectively. No surface modifier was added in Comparative Example 1, and no cross-linking agent was added in Comparative Example 2. Compared with Application Example 1, the heat-resistant polylactic acid prepared in Application Example 1 and Application Example 2 had a lower heat-resistant temperature, a lower tensile strength and a lower fracture strain, a slower crystallization rate, and a weakened nucleation effect.
[0113] The nucleating agent used in Application Example 18 is made from Comparative Example 3, and the mass ratio of the nucleating agent to the polylactic acid is 1:20. Compared with Application Example 1, the polylactic acid prepared in Application Example 18 has poor mechanical strength and a lower heat resistance temperature than that in Application Example 1.
[0114] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing an inorganic nucleating agent, It is characterized in that The following steps are involved: Preparation of composite modifier: weigh the surface modifier and the cross-linking agent in a mass ratio of 1-5:1, then add them to an acetone or anhydrous ethanol solution, mix them evenly, and prepare a composite modifier. The volume of the solution is 2-4 times the total volume of the surface modifier and the cross-linking agent; Oyster shell powder modification: take oyster shell powder, add the composite modifier thereto while stirring, mix evenly, filter, and vacuum dry to prepare an inorganic nucleating agent, wherein the addition amount of the composite modifier is 0.3-3% of the oyster shell powder; The cross-linking agent is selected from one of bismaleimide and polycarbodiimide; The surface modifier is selected from one of an aluminate coupling agent, a titanate coupling agent and stearic acid; The method for preparing the oyster shell powder comprises the following steps: washing and grinding the oyster shells to prepare block oyster shells, and calcining the block at 600-700° C. for 12-24 hours to obtain the oyster shell powder; The block oyster shells are pretreated as follows before calcination: A mixed aqueous solution of sodium sulfate and barium chloride is added to the block oyster shell, stirred for 50-60 minutes, and filtered. The molar ratio of sodium sulfate to barium chloride is 1:0.9-1.1, and the mass ratio of the block oyster shell to sodium sulfate is 1:0.1-0.
15.
2. The method for preparing the inorganic nucleating agent according to claim 1, It is characterized in that The vacuum drying temperature is 80-100° C., and the drying time is 12-24 hours.
3. The method for preparing the inorganic nucleating agent according to claim 1, It is characterized in that Before the modification, the oyster shell powder is subjected to the following pretreatment: The cellulose fibers, polyacrylamide and deionized water are mixed to prepare a suspension; Adding oyster shell powder to the suspension, mixing evenly, filtering, and drying to prepare pretreated oyster shell powder; A 15-20wt% polydiallyldimethylammonium chloride solution is evenly sprayed on the surface of the pretreated oyster shell powder. After drying, the powder is immersed in a 1.5-2wt% microfibrillated cellulose solution at room temperature for 1-2 hours, taken out, and dried at 100-110°C for 1.5-2 hours.
4. The method for preparing the inorganic nucleating agent according to claim 3, It is characterized in that When the oyster shell powder is pretreated, the weight parts of each raw material are as follows: 1-1.5 parts of cellulose fiber, 0.1-0.2 parts of polyacrylamide, 10-15 parts of deionized water, 3-5 parts of oyster shell powder, 0.5-1 parts of polydiallyldimethylammonium chloride solution, and 5-8.5 parts of microfibrillated cellulose.
5. An inorganic nucleating agent, It is characterized in that The inorganic nucleating agent is prepared by the preparation method of the inorganic nucleating agent according to any one of claims 1 to 4.
6. A heat-resistant polylactic acid, It is characterized in that An inorganic nucleating agent prepared by the preparation method of the inorganic nucleating agent according to any one of claims 1 to 4.
7. The heat-resistant polylactic acid according to claim 6, It is characterized in that The preparation method of the heat-resistant polylactic acid is: The polylactic acid is dried at 80-85° C. for 10-12 hours, and then mixed evenly with an inorganic nucleating agent in a mass ratio of 99.7:0.3-97:3, and granulated to obtain heat-resistant polylactic acid.
